2002
DOI: 10.1034/j.1600-065x.2002.19010.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomics‐based approaches to gene discovery in innate immunity

Abstract: The completion of draft sequences of the human and mouse genomes offers many opportunities for gene discovery in the field of immunology through the application of the methods of computational genomics. One arm of the innate immune system includes the antimicrobial peptides that protect multicellular organisms from a diverse spectrum of microorganisms. The beta-defensins comprise an important family of mammalian antimicrobial peptides. To better define the beta-defensin gene family, we developed an approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 61 publications
(86 reference statements)
0
24
0
1
Order By: Relevance
“…In contrast, the human b-defensins (HBDs) are predominantly epithelial products. HBD1-4 are the best characterized, although many additional defensin genes have been identified (Scheetz et al 2002, Yamaguchi et al 2002. HBD1-3 are widely expressed at epithelial surfaces, whereas HBD4 has more restricted expression, found in testis, stomach, uterus, neutrophils, thyroid, and kidney (Garcia et al 2001b).…”
Section: Defensinsmentioning
confidence: 99%
“…In contrast, the human b-defensins (HBDs) are predominantly epithelial products. HBD1-4 are the best characterized, although many additional defensin genes have been identified (Scheetz et al 2002, Yamaguchi et al 2002. HBD1-3 are widely expressed at epithelial surfaces, whereas HBD4 has more restricted expression, found in testis, stomach, uterus, neutrophils, thyroid, and kidney (Garcia et al 2001b).…”
Section: Defensinsmentioning
confidence: 99%
“…Many homologous genes are clustered in genomes and evolutionarily conserved in syntenic segments cross-species, 1,2) including immunoglobulin genes 3) and chemosensory receptor genes. 4) As more genomes are sequenced, more syntenic clustered genes will be identified through comparative genomics, which will dramatically enhance understanding of the significance of functional genomes in the physiology and pathophysiology of life.…”
mentioning
confidence: 99%
“…It has been shown recently that -amino acid residues bearing side chains branched at the first carbon have a strong 3 14 helix propensity [155,156]. The helix stability can be significantly enhanced by acylating the free amino terminus of oligoureas [157]. Although the amide bond is undoubtedly a consensual motif for the elaboration of peptidomimetics folding oligomers ("foldamers"), it was shown that the urea moiety, by its capacity to form auto-complementarities and bidirectional hydrogen bonds can be substituted for the amide linkage to generate oligomeric strands with strong propensity for helix formation [158,159].…”
Section: N N -Linked Oligoureasmentioning
confidence: 99%
“…Recently researchers attempted to model antimicrobial peptide by QSAR and other in silico methods. For example a HMM (Hidden Markov Model) based method has been developed for searching conserved motifs of -defensin family in genome databases [157]. Combinatorial chemistry, high-throughput screening, and analogous techniques have become powerful tools to promote drug discovery in peptidomimetics research.…”
Section: Design and Modeling Of Peptidomimeticsmentioning
confidence: 99%